Sixth Meeting of the Standing Committee of the National Development Council Summary Record - Planning Commission (Planning Commission, 1958)
The Chairman observed that the potential for increasing food production was enormously greater than 25 per cent. There was limitless scope for stepping up food production in the country. In this connection to referred to the opinion expressed by Dr. C. E. Kellog, head of the Soil Survey Division in the U.S.A., that if proper soil conservation practices were applied to land in India, production could be increased three to four times. A similar opinion was expressed in a recent survey issued by the World Bank. The Chairman said that organised effort was required and the best approach to the problem was through the Community Development Projects provided that agency was properly utilised.
Government of India Planning Commission
Government of India Planning Commission